Schriften zur Universitätsidee - Immel, Oliver (Karl Jaspers Gesamtausgabe. Werke, 2019)
For the first time, this volume gathers all of Jasper's texts concerning university that had been published by himself. The annotations of the edition provide valuable insights into the meaning of specific passages, the historical and intellectual context of Jasper's ideas, and the genesis of his manuscripts.